2018
DOI: 10.12944/crnfsj.6.2.06
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Antioxidant Properties and Isoflavones of Tempeh Fermented in Two Different Wrapping Materials

Abstract: Tempeh is an Indonesian traditional fermented soybean food that is well known for its nutritional value and health benefit. This study aimed to evaluate the effects of two commonly used packaging materials in tempeh production, namely banana leaf and polyethylene bag, on the antioxidant properties. Isoflavones, include daidzein and genistein, of tempeh fermented in banana leaf (TBL) and polyethylene bag (TP) were analysed with high-performance liquid chromatography. Total phenolic content and antioxidant activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…However, these lignocellulosic residues are usually not valorized [6][7][8]. Banana leaves can be used as packaging for certain foods [9], but conventionally they are left on the plantation ground. This practice is thought to benefit the crop; however, it has been determined that it can cause a nutritional imbalance in the plant [10], in addition to generating environmental and health problems [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, these lignocellulosic residues are usually not valorized [6][7][8]. Banana leaves can be used as packaging for certain foods [9], but conventionally they are left on the plantation ground. This practice is thought to benefit the crop; however, it has been determined that it can cause a nutritional imbalance in the plant [10], in addition to generating environmental and health problems [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This result similar to research conducted by Hashim that compared two materials packaging, polyethylene bag and banana leaf. The result showed that tempeh which wrapped by polyethylene bag enhanced the polyphenolic components released through the fermentation process [25]. In current study, tempeh which wrapped by combination of banana leaves and polyethylene bag (PBBL) has a higher antioxidant activity value than PB and BL.…”
Section: Resultsmentioning
confidence: 78%
“…Ekstrak tempe yang diperoleh dibuat seri pengenceran 20 mg/ml, 40 mg/ml, 60 mg/ml, dan 80 mg/ml. Kemudian, kekuatan antioksidan pada tempe dianalisis dengan magacu pada penelitian Hashim et al (2018) dengan modifikasi. Sebanyak 3 ml ekstrak sampel tempe diambil kemudian dimasukkan dalam botol kacadan ditambahkan 1 ml larutan DPPH (50 ppm) dan dihomogenkan.…”
Section: Metode/ Pelaksanaanunclassified